Optimization, physicochemical stability and in vivo study of alginate-chitosan composites as nanocarriers for low molecular weight angiotensin I-converting enzyme (ACE)-inhibitory peptide - Auwal, Shehu Muhammad; Ghanisma, Siti Balqis Muhammad; Saari, Nazamid (Taiwan Food and Drug Administration, 2024)
Chitosan and alginate, are non-toxic and biodegradable polymers used to enhance the stability of biotherapeutics by loading them into nanocarriers. In this study, the stone fish-derived low molecular weight peptide (Ala-Leu-Gly-Pro-Gln-Phe-Tyr), exhibited an in vitro ACE-inhibitory activity of 94.43 ± 2.05% and an IC50 of 0.012 ± 0.001 mM. The peptide was encapsulated via ionic gelation with alginate followed by polyelectrolyte complexation with chitosan. The resulting ACE-inhibitory peptide-loaded alginate-chitosan nanoparticles (ACE-I-ALG-CS NPs) were optimized to achieve small particle size (212.60 nm) and high encapsulation efficiency (EE, 74.48%). This was based on an optimum chitosan concentration (0.420%w/v), homogenization speed (6000 rpm), and homogenization time (30 min) using Box Behnken experimental design (BBED). Characterization of the ACE-I-ALG-CS NPs revealed a spherical, monodispersed morphology with high physicochemical stability during storage at 2°C, 7°C, and 12°C for 12 weeks. Moreover, the in vivo study conducted on spontaneously hypertensive rats (SHRs) demonstrated a significantly higher (p < 0.05) systolic blood pressure (SBP)-lowering effect of the ACE-I-ALG-CS NPs compared to captopril and unencapsulated peptide. Hence, alginate and chitosan can be used as biocompatible coating materials to enhance the stability and in vivo anti-hypertensive effect of Ala-Leu-Gly-Pro-Gln-Phe-Tyr through encapsulation, thereby making it potentially valuable for various applications in pharmaceuticals and food industry.